Characterizing Social Interactions and Grouping Patterns of Sumatran Orangutans (Pongo abelii) in the Gunung Leuser National Park, Sumatra - JITO SUGARDJITO (Biodiversitas Journal of Biological Diversity, 2009)
The character of social interactions and grouping patterns of Sumatran orangutans (Pongo abelii) have been studied in Ketambe research station of the Gunung Leuser National Park, Sumatra. A total number of 141 groupings and 47 incidences of interactive behavior were observed during the course of study. The character of groups (feeding group or travel-band) and the type of food trees (fig tree or fruit tree) appear to influence the interactive behavior of individual orangutans. Intolerance behavior has been characterized by feeding group in large fig trees, whereas tolerance and sexual behavior were shown mostly in travel-band.Key words: feeding group, travel-band, social interaction, Sumatran orangutan, Pongo abelii.